Determination Of Flood Load On Bridge Deck - Kua, Chin Tong (Universiti Sains Malaysia, 2017)
Many bridges were damaged during flood worldwide including the recent flood happened in East Coast of Peninsular Malaysia in December 2014. The fundamental causes of bridge failure during flooding are reviewed. The main objective of this numerical simulation based research are to determine the effect of various flow depths, flow velocities and elevations of the five-girder bridge deck to the hydrodynamic loading on bridge deck during flood events. Moreover, the relationship between the drag coefficient (CD), lift coefficient (CL), moment coefficient (CM) with respect to the inundation ratio (h*), proximity ratio (Pr) and Froude number (Fr) were developed. The range of the flood velocity simulated in this study was 1 m/s to 8.22 m/s and the flow depth of 5 m to 14.3 m was considered. The vertical clearance of the bridge deck is within the range of 1.5 m to 6.0 m. A physical experiment consisting partially submerged and fully submerged cases was conducted to validate the numerical results. From the numerical analysis, the graphs of the drag coefficient, lift coefficient and moment coefficient with respect to inundation ratio and Froude number were plotted. For the relationship with inundation ratio, drag and lift coefficient have a range of about 0.3 to 5.2 and -2.4 to nearly 0, respectively. Moment coefficients obtained from this study are in the range of 0.3 to 14.1. Lift and moment coefficient with respect to the proximity ratio are mostly in the range -2 to 2 and -6 to 15. The drag coefficient have all positive value in the range of 0.5 to 5 for the relationship with proximity ratio. The results of this study are useful for engineers to estimate the hydrodynamic loadings on bridge deck in designing new or retrofitting existing bridge so that it can withstand the hydrodynamic forces under partially or completely inundated cases.